Free Vibration Characteristics of Elastically Supported Pipe Conveying Fluid - Al-Hilli, Ali H.; Ntayeesh, Thaier J. (Nahrain University College of Engineering Journal, 2017)
In this study, the effect of support values onthe natural frequency and critical flow velocityof a straight pipe conveying laminar flowingfluid is studied. The aim of this work isderiving a new analytical model to perform ageneral study to investigate the dynamicbehavior of a pipe under general boundaryconditions by considering the supports ascompliant material with linear and rotationalsprings. This model describes both theclassical (simply support, free, built, guide)and the restrained boundary condition and it isnot required to derive a new frequencyequation if the boundary conditions is changed,also the result will be near to reality byknowing the physical parameters for thecompliant material and the pipe.